The Development of the Student’s Reading Practice set for Reading Aloud, Diphthongs and Poetry Secondary 1, Bang Pa-in School “Rachanukroh 1” - Lakul, Anan; Yahom, Ampornphan (Dhammathas Academic Journal, 2024)
The purposes of this research were 1) develop a set of exercises for improving the pronunciation skills of diphthongs for Secondary education 1/5 students at Bang Pa-in "Rachanukroh 1" School to meet the 70/70 criteria, and 2) compare the scores of diphthong pronunciation skills of students before and after learning with the set of exercises for diphthong pronunciation. This is quantitative research with a target group of 30 Secondary education 1/5 students at Bang Pa-in "Rachanukroh 1" School. The statistics used in data analysis include percentage, mean, and standard deviation. Data is analyzed using content analysis. The results revealed that: 1. The set of exercises for diphthong pronunciation developed for Secondary education 1/5 students is effective at 70/70. The results obtained are 74.63/80.00, meeting the 70/70 criteria. 2. The comparison of diphthong pronunciation skills scores of students before and after learning with the set of exercises for diphthong pronunciation in poetry for Secondary education 1/5 students, shows that students have higher diphthong pronunciation skills scores after learning than before learning. The analysis of the average scores of the pre-test and post-test shows that the quality meets the specified criteria. Students scored a total of 149 points before using the set of exercises for diphthong pronunciation, with an average of 4.96, representing 49.67%. After using the set of exercises for diphthong pronunciation, students scored a total of 240 points, with an average of 8.00, representing 80.00%. This indicates an increase of 30.33% in the scores after using the set of exercises for diphthong pronunciation.